2017
DOI: 10.18632/oncotarget.22056
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of RNF187 induces hepatocellular carcinoma cell epithelial to mesenchymal transitions

Abstract: Ring finger protein 187 (RNF187) has been identified to be a co-activator linking c Jun to Ras signaling. However, the expression and function of RNF187 in hepatocellular carcinomas (HCC) remains unclear. Here, we tried to determine the expression and roles of RNF187 in hepatocellular carcinomas (HCC).The expression of RNF187 was determined in HCC tissues and cell lines, and we found that RNF187 expressed highly in HCC tissues compared with the corresponding adjacent liver tissues both in mRNA and protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…Previous studies showed that RNF187 is required for AP-1 mediated cell proliferation 20 . Besides recent studies showed that RNF187 could play an oncogenic role in several cancers [20][21][22][23] . For example, RNF187 could promote liver cancer progression via Norch1 signaling 21 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies showed that RNF187 is required for AP-1 mediated cell proliferation 20 . Besides recent studies showed that RNF187 could play an oncogenic role in several cancers [20][21][22][23] . For example, RNF187 could promote liver cancer progression via Norch1 signaling 21 .…”
Section: Introductionmentioning
confidence: 94%
“…Besides recent studies showed that RNF187 could play an oncogenic role in several cancers [20][21][22][23] . For example, RNF187 could promote liver cancer progression via Norch1 signaling 21 . However, in our current study, RNF187 functions as a tumor suppressor in TNBC progression.…”
Section: Introductionmentioning
confidence: 94%
“…25 In addition, FBW7, as a RING E3 ubiquitin ligase, can also cause ubiquitination and degradation of YAP at the k48 site. 26 Our current study indicated that 15,17,18 Our data showed that RACO-…”
Section: F I G U R E 3 Raco-1 Inhibits Cell Migration and Invasion Thmentioning
confidence: 54%
“…Polyclonal rabbit anti-human RNF187 (1:200; Novus Biologicals, Cambridge, UK) was used to detect the RNF187 protein. RNF187 expression was evaluated according to the intensity and ratio of positive tumor cells as the previously described [6,13,16]. The two levels of RNF187 intensity of were classified according to the mean area of positive staining, and the cutoff value was 50% of tumor section, the ≥50 percent was positive, and negative was < 50 percent.…”
Section: Tissue Microarrays and Immunohistochemistrymentioning
confidence: 99%
“…E3 ubiquitin ligases (E3s) are critical importance due to not only transfer ubiquitin to specific substrates [5]. Ring finger protein 187 (RNF187), a RING domain-containing ubiquitin E3 ligase, was lately verified to overexpressed in hepatocellular carcinoma and non-small cell lung carcinoma and advanced tumor development by inducing tumor cell epithelial-mesenchymal transition (EMT) [6,7]. Furthermore, RNF187 knockout was revealed to suppress the cellular proliferation via inhibiting the transcription of AP-1-related genes, and RNF187 overexpression activated Wnt and Ras pathways to accelerate the tumor formation in colon epithelial tumor [8].…”
Section: Introductionmentioning
confidence: 99%